Large squamous papilloma in unusual site: A case report and review of the literature - Goud, Tejaswini Naganur; Mohammad, Ali I; Panchaksharappa, Mamatha G; Annigeri, Rajeshwari G (Indian Journal of Case Reports, 2019)
Squamous papilloma is a benign proliferation of the stratified squamous epithelium, resulting in a papillary mass, which appears as sessile or pedunculated growth with cauliflower-like projection. The most common sites are palate, uvula followed by tongue and lip. Most of the time it usually presents as a solitary, exophytic growth with an average size of less than 1 cm.Here, we report the case of a 28-years-old male patient presented with a solitary sessile, white growth with multiple papillary projections on the right buccal mucosa measuring approximately 4 x 3 cm. An incisional biopsy followed by surgical excision of the lesion was performed confirming the diagnosis of squamous papilloma. This paper highlights a case of unusually large-sized papilloma in an uncommon site.